2015
DOI: 10.1080/00423114.2015.1020815
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact of locomotive creep control on wear under changing contact conditions

Abstract: This paper presents the locomotive traction controller performance with respect to the track wear under different operation conditions. In particular, an investigation into the dynamic response of a locomotive under changing wheel-rail friction conditions is performed with an aim to determine the effect of controller setting on track wear. Simulation using a full-scale longitudinal-vertical locomotive dynamic model shows that the appropriately designed creep threshold, controller, settings can effectively main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The influences of train dynamics on locomotive wheel wear and RCF are also reflected by the interaction between train dynamics and traction control systems. 1719 It is easy to understand that, under different in-train forces, different traction control commands are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of train dynamics on locomotive wheel wear and RCF are also reflected by the interaction between train dynamics and traction control systems. 1719 It is easy to understand that, under different in-train forces, different traction control commands are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesive control algorithms can be divided into two types according to the maximum adhesion point tracking: readhesion control and optimized adhesion control [5].…”
Section: Introductionmentioning
confidence: 99%
“…Locomotive dynamic modelling A 2-dimensional locomotive diagram is as shown in Fig.1b, including longitudinal, vertical and pitch modes of locomotive operation, and is detailed in [8]. This model has 21 degrees of freedom (DOF), including 9 DOF on the longitudinal, vertical and pitch motions of locomotive body and its two bogies, and 12 DOF on vertical and rotating motions of six wheelsets.…”
Section: 1mentioning
confidence: 99%
“…In general, locomotives with new AC traction motors are operated with much higher continuous traction forces and adhesion levels compared to locomotives with DC motors. Recently, it was shown that the rail/wheel contact mechanics and the dynamic response caused by a change in contact conditions of the new AC driven locomotives is significantly different to the DC models [8]. Thus it is necessary to investigate and compare the effect of the AC and DC drives dynamics on the wear growth independently by establishing detailed electric dynamic models with AC and DC drive models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation